Management of post CABG sternal oesteomyelitis (Bangladesh Journal of Plastic Surgery, 2011)
Two cases of post CABG sternal wound with sternal osteomyelitis were managed in plastic surgery unit from year 2007-2008. One of them was male and other was female. Both were diabetic. The male one had multiple sinus tracts with discharge and the female one had well granulated wound with discharge. Both the cases were managed by adequate debridement of the wound with removal of some loose sternal wire and placement of a cutaneous flap over the wound. In both cases, the flaps survived well, infection was completely resolved. The scar over the chest wall was cosmetically acceptable. DOI: http://dx.doi.org/10.3329/bdjps.v1i2.8804 BDJPS 2010; 1(2): 38-41